2018
DOI: 10.1002/ana.25128
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell plasticity in the evolution of central nervous system autoimmunity

Abstract: These observations demonstrate the heterogeneity of CNS myeloid cells, their evolution during the course of autoimmune demyelinating disease, and their plasticity on the single cell level. Future therapeutic strategies for disease modification in individuals with MS may be focused on accelerating the transition of CNS myeloid cells from a proinflammatory to a noninflammatory phenotype. Ann Neurol 2018;83:131-141.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…Pro-inflammatory myeloid cells during the pathogenesis of EAE have been described previously. Along these lines, central roles were reported for CCR2 + myeloid cells 44 , tissue resident classical DC 45 , microglia vs peripherally seeded monocytederived DC 20 , and pro inflammatory iNOS + macrophages vs anti-inflammatory Arg-1 + macrophages 45 . Our observations add to the complexity of categorizing myeloid cell populations into DC or monocytes/macrophages based on surface markers alone.…”
Section: Discussionmentioning
confidence: 96%
“…Pro-inflammatory myeloid cells during the pathogenesis of EAE have been described previously. Along these lines, central roles were reported for CCR2 + myeloid cells 44 , tissue resident classical DC 45 , microglia vs peripherally seeded monocytederived DC 20 , and pro inflammatory iNOS + macrophages vs anti-inflammatory Arg-1 + macrophages 45 . Our observations add to the complexity of categorizing myeloid cell populations into DC or monocytes/macrophages based on surface markers alone.…”
Section: Discussionmentioning
confidence: 96%
“…Myeloid cell activation in the CNS is a hallmark of inflammatory lesions in EAE and MS, where myeloid cells of the brain continuously scan their environment, mediating both detrimental and tissue homeostatic functions, presumably depending on the context (Giles et al, 2018; Heneka et al, 2014; Jolivel et al, 2015; Nimmerjahn et al, 2005). Although it is well known that pathogenic Th17 cells invade the CNS during MS and EAE, thereby mediating inflammation and neuronal degeneration (Dendrou et al, 2015; Goverman, 2009), whether they engage resident myeloid cells directly has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Variable roles of resident myeloid cells of the brain have been reported in both the healthy and diseased state (Giles et al, 2018; Schafer and Stevens, 2015; Shemer et al, 2015). Aside from defending against invading pathogens, they also use their phagocytic capacity to clear cellular debris, infectious agents, or neurons undergoing programmed cell death, thereby attempting to maintain tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, promoting the polarization of macrophages to alternative activation states may be a strategy for the treatment of type 2 diabetes . Giles et al found that in multiple sclerosis (MS) and engineered autoimmune encephalomyelitis (EAE) animal models, molecular phenotypic changes occur in the main infiltrating myeloid cells and microglia in the central nervous system (CNS), including differences in the expression levels of pro‐inflammatory markers (iNOS) and noninflammatory markers (CD206 and Arg1), during the progression from the EAE activity period to the remission period. Based on these observations, the research team believes that accelerating the transformation of CNS myeloid cells from a pro‐inflammatory phenotype to a noninflammatory phenotype could be a central strategy for improving the disease status of MS patients in future.…”
Section: Relationships Between Macrophage Heterogeneity and Diseasementioning
confidence: 99%